PENGARUH PENGALAMAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PADA PT. SUMBER SAWIT SEJAHTERA KABUPATEN PELALAWAN - Ayu Aninda Septiara; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the effect of work experience and work motivation on the performance of production employees at PT. Source of Prosperous Palm Oil in Pelalawan Regency. This research is located at PT. Source of Prosperous Palm Oil in Pelalawan Regency. The population in this study includes all employees of the production department at PT. Sumber Sawit Sejahtera, totaling 85 employees. Data analysis was performed using statistical analysis with the help of SPSS. The sampling technique used is the census method and the data testing technique in this study includes validity test, reliability test, determination test, simple linear regression analysis, simple linear regression analysis, t-test, and F-test to test and prove the hypothesis. The results showed that work experience and work motivation had a significant influence on the performance of employees in the production department at PT. Prosperous Palm Resources. Based on the results of the study, the R square value of 0.526 means that 52.6% of the variables of Work Experience and Work Motivation affect the Performance of Production Section Employees at PT. Source of Prosperous Palm Oil in Pelalawan Regency. Keywords: Work Experience, Work Motivation, Employee Performance